INDICATORS FOR ACHIEVING THE SUCCESS OF MIDWIVES' EFFECTIVE COMMUNICATION SKILLS: A REVIEW FROM MIDWIFERY SERVICES - Rima Wirenviona; Fani Syinthia Rahmi; Nurul Fatimah Susanti (Adisam Publisher, 2026)
Effective communication is a fundamental skill in midwifery, playing a crucial role in building trust, ensuring the safety of patients, and enhancing the health outcomes for both mothers and newborns. This review of existing literature focuses on studies that evaluate the communication skills of midwives across different healthcare settings. The research included articles published from 2015 to 2025, sourced from databases like PubMed, ScienceDirect, and Google Scholar. The findings show that midwives use various forms of communication, including spoken words, body language, written notes, and interactions with others, all of which greatly influence the quality of care they provide. While many studies indicate that midwives often show empathy and are good listeners, there are still challenges in areas such as being confident in expressing needs, maintaining proper records, and communicating effectively across different cultures. It is important for midwives to recognize the signs of effective communication in their work, such as possessing strong communication abilities, understanding human behavior, having training in effective communication techniques, and being able to use technology. The review concludes that ongoing learning and development in communication skills are vital for improving midwives' abilities and delivering care that is centered around the needs of patients.